اردو تفاسیر میں سائنسی اسلوبِ استدلال : ڈاکٹر اسرار احمد کی تفسیر بیان القران کا مطالعہ (Al-Qamar, 2018)
In many Urdu commentaries of the Quran scientific style of reasoning has been adopted. This article studies Dr. Israr Ahmad’s tafsīr Bayān al-Quran from the referred perspective. It concludes that Dr. Israr has stated very important points in the interpretation of some verses regarding the understanding of the Quran in scientific way, which has made it easier to understand the relevant verses and remove the misconceptions found in this regard.
Keywords: Scientific Style of reasoning; Urdu Commentaries of Quran; Dr. Israr Ahmed; “Bayān al-Quran